1998
DOI: 10.1021/om971041f
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ligand Effects through Isoequilibrium Phenomena:  The Quantitative Analysis of Ligand Effects

Abstract: Analysis of the E°values of the η-Cp(CO)(L)Fe(COMe) +/o couple (measured via cyclic voltammetry at 229, 252, 264, 273, and 293 K in acetonitrile/0.1 M TBAH) has revealed different isoequilibrium behavior for P(p-XC 6 H 4 ) 3 and PR 3 . We classify ligands as a family when they exhibit a single isoequilibrium point. A family of ligands affects a property via variation of a single, or effectively single, parameter. Thus, through isoequilibrium behavior, we have an unambiguous way to identify families, which in q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…The next step is to get an estimate of the π parameters for P(OMe) 3 and P(OCH 2 ) 3 CEt. From the analysis of ∆SЊ and ∆HЊ for the η-Cp(CO)(L)Fe(COMe) ϩ/0 couple we know that the aryl effect in ∆GЊ vanishes at 320 K (the E ar isoequilibrium temperature [83][84][85][86] ). Thus, we calculated ∆GЊ (320 K) and analyzed the data for the phosphines in terms of χ d and θ only (entry 6, Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The next step is to get an estimate of the π parameters for P(OMe) 3 and P(OCH 2 ) 3 CEt. From the analysis of ∆SЊ and ∆HЊ for the η-Cp(CO)(L)Fe(COMe) ϩ/0 couple we know that the aryl effect in ∆GЊ vanishes at 320 K (the E ar isoequilibrium temperature [83][84][85][86] ). Thus, we calculated ∆GЊ (320 K) and analyzed the data for the phosphines in terms of χ d and θ only (entry 6, Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…It is, therefore, of interest to find sets of data that can be used both to derive values for the various coefficients contained in equations such as eqn ( 1)-( 3), and to investigate their temperature dependence. Suitable data have been reported by Fernandez et al 30,31,45 E1 values for the reduction reactions shown in eqn (14) were measured to an excellent precision, estimated to be AE0.7 mV for a large selection of P-donor ligands, L, with reference to the reduction of [(Z 5 -C 5 H 5 )(Z 5 -C 5 H 4 COMe)Fe] + .…”
Section: The Physical Significance Of Isokinetic and Isoequilibrium T...mentioning
confidence: 75%
“…It can then be shown 30,38 that the LFER can be expressed as in eqn (8), where x = À2.303R, so that a, b and g are given by eqn ( 9), (10) and (11), respectively.…”
Section: Linear Free Energy Relationships (Lfers)mentioning
confidence: 99%
See 1 more Smart Citation
“… a Δ H ° values are in kJ mol -1 , and Δ S ° values are in J K -1 mol -1 . The Δ H ° and Δ S ° values are relative to the reduction of acetylferrocene (see ref ). b These values refer to the (η-Cp)(CO)(L)Fe(COMe) +/0 redox couple relative to the (η-Cp)(η-C 5 H 4 COMe)Fe +/0 redox couple.…”
Section: Introductionmentioning
confidence: 99%